A Study on the Association Between Polymorphisms in the Cytochrome P450 Family 17 Subfamily A Member 1 Gene Region and Type 2 Diabetes Mellitus in Han Chinese - Wang, Long; Niu, Yu-Ming; Wu, Shi-Shi; Zhang, Chao; Zhou, Li; Zuo, Hong-Xia; Wang, Peng (Frontiers in Endocrinology, 2018)
Background: Cytochrome P450 family 17 subfamily A member 1 (CYP17A1) gene encodes a key enzyme in the synthesis and metabolism of steroid hormones and has been associated with various factors, such as hypertension, insulin resistance, and polycystic ovary syndrome. However, whether the gene was associated with type 2 diabetes mellitus (T2DM) has not been reported yet. Therefore, we sought to investigate whether CYP17A1 was associated with T2DM and related traits among Han Chinese. Methods: Three tagging single nucleotide polymorphisms (rs1004467, rs17115149, and rs12413409), in the CYP17A1 gene region were selected and genotyped in a case control study that included 440 diabetes and 1,320 control subjects. Effects of genetic loci were studied using univariate unconditional logistic regression and multivariate logistic regression analysis adjusted for age, sex, family history, body mass index, smoking, and drinking. Bioinformatics analysis was also conducted using the GEO DataSets and PROMO database to gain hints of possible mechanism. Results: Rs17115149 and rs12413409 polymorphisms were significantly associated with the risk of T2DM, even after adjusting for age, sex, family history, body mass index, smoking, and drinking. In stratified analyses, rs1004467 and rs12413409 showed significant association with T2DM in the older age group (≥65 years) and, in the case of rs12413409, the risk of T2DM was significant in men but not in women. Rs17115149 had significant association with T2DM in the hypertension subgroup, and rs12413409 in the non-hypertension subgroup. Moreover, rs12413409 showed significant association with plasma glucose levels in the recessive model (P=0.020) among subjects not taking hypoglycemic measures. Bioinformatics analysis revealed significantly higher CYP17A1 gene expression in T2DM patients compared to healthy controls. Finally, the mutant T allele of the rs17115149 polymorphism allowed binding to the RBP-Jkappa transcription factor. Conclusion: This is the first report to identify that variants rs1004467, rs17115149, and rs12413409 of CYP17A1, are related to plasma glucose levels and T2DM among Han Chinese. Our results suggest that CYP17A1 might constitute a risk gene for progression to T2DM.